The Mediating Role of Employee Satisfaction: An Analysis of Cost Changes, Work Quality, and Company Image on Employee Loyalty in Batam Cafes - Yuli Indah Fajar Dini; Inayah Alifia Fajar (Yayasan Riset dan Pengembangan Intelektual, 2023)
This study aims to determine the effect of Cost Change, Work Quality, and Company Image On Loyality of Employee Cafe in Batam With Employee Satisfaction as A Mediation Variable. The population in this study were the Employees Café in Batam with a total of 510 respondents as a sample conducted from February to June 2023 using online and offline questionnaire. The research data was analyzed using SmartPLS version 3 application. The cost change variable has no effect and does not significantly influence the employee satisfaction variable. The work quality variable shows a positive and significant influence in influencing the employee satisfaction variable. The corporate image variable shows a positive and significant influence in influencing the employee satisfaction variable. The cost change variable has no effect and does not significantly influence the employee loyalty variable. The work quality variable shows a significant positive influence in influencing the employee loyalty variable. The corporate image variable shows a significant positive influence in influencing the employee loyalty variable. The employee satisfaction variable shows a positive but not significant influence in influencing the employee loyalty variable. The cost change variable indirectly has no effect and does not significantly affect the employee loyalty variable. The work quality variable indirectly has a positive but not significant influence on the employee loyalty variable. The company image variable indirectly has no effect and is not significant on the employee loyalty variable.